Europe’s Legitimacy Crisis - Longo, M. author. aut Link
VIII, 150 p.
Keywords: Sharp in focus and succinct in analysis, this Pivot examines the latest developments and scholarly debates surrounding the sources of the European Union's crisis of legitimacy and possible solutions. It examines not only the financial and economic dimensions of the current crisis, but also those crises at the heart of the EU integration project.